Crohn's disease: factors associated with exposure to high levels of diagnostic radiation. Issue 11 (28th April 2008) - Desmond, A N; O'Regan, K; Curran, C; McWilliams, S; Fitzgerald, T; Maher, M M; Shanahan, F
Abstract : Aims: Exposure to diagnostic radiation may be associated with increased risk of malignancy. The aims of this study were to (1) examine patterns of use of imaging in Crohn's disease; (2) quantify the cumulative effective dose (CED) of diagnostic radiation received by patients; and (3) identify patients at greatest risk of exposure to high levels of diagnostic radiation. Methods: 409 patients with Crohn's disease were identified at a tertiary centre. CED was calculated retrospectively from imaging performed between July 1992 and June 2007. High exposure was defined as CED>75 mSv, an exposure level which has been reported to increase cancer mortality by 7.3%. Complete data were available for 399 patients. 45 were excluded (20 attended outside the study period, 25 were primarily managed at other centres). Results: Use of computed tomography increased significantly and accounted for 77.2% of diagnostic radiation. Mean CED was 36.1 mSv and exceeded 75 mSv in 15.5% of patients. Factors associated with high cumulative exposure were: age <17 years at diagnosis (hazard ratio 2.1, confidence interval (CI) 1.1 to 4.1), upper gastrointestinal tract disease (odds ratio (OR) 2.4, CI 1.2 to 4.9), penetrating disease (OR 2.0, CI 1.0 to 3.9) and requirement for intravenous steroids (OR 3.7, CI 2.0 to 6.6); infliximab (OR 2.3, CI 1.2 to 4.4); or multiple (>1) surgeries (OR 2.7, CI 1.4 to 5.4). Conclusions: Identifiable subsets of patients with Crohn's disease are at risk of exposure to significant amounts of diagnostic radiation. Given the background risk of neoplasia and exposure to potentially synergistic agents such as purine analogues and other immune modulators, specialist centres should develop low-radiation imaging protocols.